Prerequisites for HACCP in poultry processing in Maputo, Mozambique - Muchangos, A.C.; Makita, K.; Grace, Delia; Matusse, H.; McCrindle, C.M.E. (University of Pretoria, 2012)
Poultry is a major component of the diet and a valuable and affordable source of protein for all levels of society. It is unknown whether poultry meat consumption contributes to diarrheal diseases, an important cause of mortalities. This study used participatory risk analysis to investigate the value chains for poultry processing in Maputo, indicating possible stages at which there was a risk of microbiological hazards that could influence safety of the final product. The method included semi structured interviews, various focus group discussions and observation of poultry processing in both formal abattoirs and informal slaughter (farms and live bird markets). The magnitude of the risk of microbiological hazards was estimated using laboratory analysis, specifically 3M™ Petrifilm™ Plates for E coli Type I, Coliforms and plate count as indicators of contamination to assess the compliance with GHP and GMP, relevant pre-requisites for HACCP. 330 samples of poultry carcass were randomly collected from abattoirs, live bird markets and farms. The contamination rate with E. coli Type I was significantly higher in markets (63%) than abattoirs (39%) and farms (40%). Suggesting a higher likelihood of risk in poultry meat from live bird markets than those from the abattoir or direct from the farm. All three value chains were, however, contaminated with the faecal derived organism, which has the potential to cause food born disease in consumers. Prerequisites such as lack of processing infrastructure, inadequate waste management and poor hygiene were observed in markets. In the formal abattoir, disinfection of surface and utensils, ablutions or hand disinfection and chilling system was found to be inadequate. A hygiene assessment system is proposed with a focus on those CCPs suggested by the research and participatory risk communication strategy has been developed for all those involved in the poultry chain to improve hygiene and safety of poultry meat.